Characterization of the cellar mud odor compounds and their content variation in strong aroma base Baijiu by GC/MS/O and means of molecular sensory science - Wanzhong Zhang; Xinglin Han; Deliang Wang; Wei Jiang; Ligang Hao; Yuqi Chen; Feng Zhou; Jianxiang Hu; Xinli Meng (Applied Food Research)
The aim of this work was to elucidate the specificity of the cellar mud odor compounds in strong aroma base Baijiu using gas chromatography-olfactometry-mass spectrometry analysis based on chemical and sensory profiles. Fifty-three aroma compounds in both base and commercial Baijiu were identified and quantified by comparing their MS, retention indices with those of pure standards. Odor activity values and principal component analysis were used to account for the variation in the sensory attributes of these aroma compounds. The results demonstrate that high acid and phenol contents contribute to the cellar mud aroma profiles in base strong aroma Baijiu. This approach may provide valuable information for product quality control of strong aroma Baijiu products.